Activation of Nesfatin‐1‐Containing Neurones in the Hypothalamus and Brainstem by Peripheral Administration of Anorectic Hormones and Suppression of Feeding via Central Nesfatin‐1 in Rats. (19th August 2016) - Saito, R.; So, M.; Motojima, Y.; Matsuura, T.; Yoshimura, M.; Hashimoto, H.; Yamamoto, Y.; Kusuhara, K.; Ueta, Y.
Abstract : Peripheral anorectic hormones, such as glucagon‐like peptide (GLP)‐1, cholecystokinin (CCK)‐8 and leptin, suppress food intake. The newly‐identified anorectic neuropeptide, nesfatin‐1, is synthesised in both peripheral tissues and the central nervous system, particularly by various nuclei in the hypothalamus and brainstem. In the present study, we examined the effects of i.p. administration of GLP‐1 and CCK‐8 and co‐administrations of GLP‐1 and leptin at subthreshold doses as confirmed by measurement of food intake, on nesfatin‐1‐immunoreactive (‐IR) neurones in the hypothalamus and brainstem of rats by Fos immunohistochemistry. Intraperitoneal administration of GLP‐1 (100 μg/kg) caused significant increases in the number of nesfatin‐1‐IR neurones expressing Fos‐immunoreactivity in the supraoptic nucleus (SON), the area postrema (AP) and the nucleus tractus solitarii (NTS) but not in the paraventricular nucleus (PVN), the arcuate nucleus (ARC) or the lateral hypothalamic area (LHA). On the other hand, i.p. administration of CCK‐8 (50 μg/kg) resulted in marked increases in the number of nesfatin‐1‐IR neurones expressing Fos‐immunoreactivity in the SON, PVN, AP and NTS but not in the ARC or LHA. No differences in the percentage of nesfatin‐1‐IR neurones expressing Fos‐immunoreactivity in the nuclei of the hypothalamus and brainstem were observed between rats treated with saline, GLP‐1 (33 μg/kg) or leptin. However, co‐administration of GLP‐1 (33 μg/kg) and leptin resulted in significant increases in the number of nesfatin‐1‐IR neurones expressing Fos‐immunoreactivity in the AP and the NTS. Furthermore, decreased food intake induced by GLP‐1, CCK‐8 and leptin was attenuated significantly by pretreatment with i.c.v. administration of antisense nesfatin‐1. These results indicate that nesfatin‐1‐expressing neurones in the brainstem may play an important role in sensing peripheral levels of GLP‐1 and leptin in addition to CCK‐8, and also suppress food intake in rats.